Estudio inmunoelectroforetico de las proteínas séricas en niños severamente quemados - Ríos Huerta, Alex (1968)
In the past 20 years there have been considerable advances in the treatment of patients with severe burns (more than 10% of body surface area), mainly in regard to shock therapy (1, 11, 14. 16 , 21, 22), which have resulted in a significant reduction in early mortality (within the first 60 hours after trauma). This improvement is due to a better understanding of the pathophysiological mechanisms of traumatic shock, allowing new, especially referable to the proper use of balanced solutions alone or supplemented with sodium chloride plasma therapeutic approaches, which allowed decreasing the mortality in this early phase and prolonged the survival of severely burned patients.